DECOLONIZING ISLAMIC STUDIES: A VIEW FROM THE SALAFIS SCHOOL OF THOUGHT - EMORDI PROMISE JUDE; OGHENERO KANO BENSON; CHUKWUKADIBIA CHIMAUZOM EZE; CYNTHIA UKA IYADE; AYINOR AZUBUIKE (International Studies Journal)
This essay argues for a critical re-evaluation of Islamic studies, challenging the Eurocentric and Arab-centric biases that have historically shaped the field. We propose a de-colonial approach that dismantles assumptions of Arab supremacy and promotes a more inclusive understanding of Islam. Through the lens of the Salafi school of thought, a historically and geographically diverse movement within Islam, we examine the relationship between Islamic faith and Arab identity. Through the lens of critical thinking, we explore how the Salafi school both reinforces and critiques notions of Arab centrality in Islam. Furthermore, we examine potential tensions between Salafi interpretations and human autonomy and rights. Ultimately, we argue that decolonizing Islamic studies necessitates diverse perspectives, fostering a more humane, creative, and productive understanding of this global religion with over 1.8 billion adherents worldwide.